ADOBE® FLEX® 3 PROGRAMMING ACTIONSCRIPT™ 3.0 - Systems, Adobe; Systems, Adobe (Adobe Systems, 2008)
Describes fundamental programming concepts in ActionScript 3.0, including the ActionScript language, event handling, object-oriented programming, data types, regular expressions, XML (E4X), networking, and Flash Player security.